The Extent of Innovation in Philippine Business and Industry: Results of the 2021 PIDS Survey of Innovation Activities - Jose Ramon G. Albert; Francis Mark A. Quimba; Ramonette B. Serafica; Jana Flor V. Vizmanos; Neil Irwin S. Moreno; Abigail E. Andrada; Mika S. Mu\~noz; Angelo C. Hernandez (Philippine Institute for Development Studies (PIDS), 2023)
The Oslo Manual, following ideas of Schumpeter, defines innovation as "the implementation of a new or significantly improved product (good or service), or process, a new marketing method, or a new organizational method in business practices, workplace organization or external relations". With the advent of the Fourth Industrial Revolution (FIRe), governments have become even more cognizant of innovation as a major driver of economic performance, from output, to productivity, and to competitiveness. The Philippine government acknowledges its role in establishing and maintaining a conducive policy environment to encourage innovation and support the country's innovation ecosystem. Examining innovation and its relation to economic growth, the study involves the conduct and analysis of the 2021 PIDS Survey of Innovation Activities (PSIA). Unlike the first PSIA undertaken in 2015, and a pilot of the survey conducted in 2009, the 2021 PSIA provides a nationally representative reading of the entire Philippine business and industry. The survey suggests that as of 2021, a third (33.6%) of firms are innovation active, with innovation practiced more among medium and large establishments than micro- and small ones. Further, innovation is much more prevalent in Mindanao among major islands, and in ICT firms (and least in Agriculture). Aside from information on innovation activities, data on the use of digital platforms by Philippine businesses was also gathered in the 2021 PSA, in recognition of the expanding markets arising from rising digitalization and more rapid use of internet, even by micro, small and medium enterprises (MSMEs). The survey results of the 2021 PSIA are expected to be inputs on how government can be more successful in mainstreaming innovation in the country.
Keywords: 330; innovation; product innovation; process innovation; organizational innovation; marketing innovation; micro; small and medium enterprises (MSMEs); Fourth Industrial Revolution; platform economy; digital platforms